Pengaruh Perpustakaan Terhadap Sistem Pembelajaran Berbasis Student Center Learning di Universitas Hasanuddin Makassar - Darmiati Darmiati; Darmawari Nembo (Media Pustakawan, 2021)
Research purposes are to identify, analyze and describe the influence of libraries on the Student Center Learning based learning system at Hasanuddin University. This research is quantitative. The research samples students and lecturers of Hasanuddin University who took advantage of all library services. Respondents were determined using the accidental sampling method, namely whoever comes to use the library when the researcher is doing research and 50 samples from various study programs. Data collection by distributing questionnaires and documentation. The data were analyzed using multiple linear regression to prove the influence of the library on the student center learning system at Hasanuddin University. This study found that only the library service variable had a positive effect on the student center learning system at Hasanuddin University. The role of university library services in the learning system is very important because through this service students and lecturers can interact either directly or indirectly to obtain various types of information to support the learning process. However, the components of collections and information technology based on the research results have no effect. Library collections in universities are very important and must be considered. A Good collection is a collection that is complete, adequate, relevant, and updated. Information technology is important because information technology is a medium for library management activities and automatic dissemination of information. The use of technology can increase the effectiveness and efficiency of library management activities and further provide convenience and efficiency for users to find information sources.